Epigenetic in medullary thyroid cancer: the role of microRNA in tumorigenesis and prognosis. Issue 1 (January 2021) - Manso, Jacopo; Censi, Simona; Mian, Caterina
Abstract : Purpose of review: MicroRNAs emerged as pivotal regulators of cell differentiation, growth, and cell death, suggesting their implication in tumorigenesis and prognosis of cancer. In the last decades, knowledge about the alterations of microRNAs in medullary thyroid cancer (MTC) is increasing. In this review, we try to summarize the most relevant findings regarding microRNA dysregulation in MTC. Recent findings: A literature analysis was performed in MEDLINE for studies published up to August 2020. Comprehensively, at least 27 different microRNAs have been investigated in MTC showing evidence for overexpression or underexpression in comparison with normal thyroid tissue samples, healthy blood controls, or primary tumor site or hereditary form of MTC. We highlight the evidence in favor of a possible use of microRNAs for diagnosis, prognosis and treatment in MTC and their role in MTC pathogenesis. Summary: This review reveals the emerging complexity of the molecular genetic and epigenetic panorama in MTC. Further studies are needed to confirm and refine the findings on microRNA expression pattern in MTC. Thus, in the future, microRNA analysis could enter in clinical practice and may pave the way to new risk-stratification tools and novel therapeutic approaches for MTC.